HUBUNGAN ANTARA HASIL BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK DALAM MATERI AYO KITA HORMATI ORANG TUA DENGAN SIKAP BIRRUL WALIDAIN KELAS X DI MAN 1 KETAPANG - Mutmainnah (Jurnal Studi Islam Lintas Negara (Journal of Cross Border Islamic Studies), 2019)
This study aims to determine: (1) student learning outcomes in the subject of Aqidah Akhlak in the subject Come on Respect for Our Parents with the birrul walidain attitude of class X students at MAN 1 Ketapang. (2) the attitude of Birrul Walidain to class X students at MAN 1 Ketapang. (3) how big is the relationship between student learning outcomes in the subject of Aqidah Akhlak in the material Come on Respect for Our Parents with the attitude of Birrul Walidain in class X students in MAN 1 Ketapang ". This research method uses descriptive research with a quantitative approach. In the process of collecting data, researchers used questionnaires and documentation. The data analysis technique used in this study was the Produt Moment correlation statistical analysis technique. The subjects in this study were students of class X at MAN 1 Ketapang with a total sample of 40 students. From the research results, it can be concluded that: (1) The learning outcomes of Aqidah Akhlak in the material Come on Respect for Our Parents class X in MAN 1 Ketapang can be said to be very high. This is shown by the results of the calculation of the average student learning outcomes obtained through daily tests, namely 91.48 rounded to 91, which is in the range 66.70-100, meaning it is in the very high category. (2) The attitude of Birrul Walidain of class X students at MAN 1 Ketapang is very good. This is evidenced by the results of the calculation of the average questionnaire distributed to the students regarding the birrul walidain attitude, the results obtained were 88%, which is in the 80-100 interval with very good interpretations. (3) The correlation coefficient for the X and Y variables (rxy) was found to be 0.558 at the coefficient interval 0.40-0.599, which is in the moderate category, meaning that there is a significant relationship between student learning outcomes in the subject of aqidah morals in the material, let's respect parents. with the birrul walidain attitude of class X students at MAN 1 Ketapang that is equal to 31%. This is evidenced by the results of calculations using the product moment correlation formula at the 5% significance level where rh = 0.588 which is greater than rt = 0.312, meaning that Ha is accepted and Ho is rejected. So it can be concluded that the higher the student learning outcomes in the subject of Aqidah Akhlak in the material Come on, respect our parents, the better the attitude of Birrul Walidain for class X students at MAN 1 Ketapang.